Child poverty in Portugal: the crisis from children´s perspectives - Sarmento, Manuel Jacinto (2020)
As several countries went through hardships following the 2008 economic crisis, different reports have suggested that specific generational groups – such as children and adolescents – have been hit the hardest. Amongst these concerns, different indicators have strengthened the idea that children were the most visible face of poverty and of global well-being indicators that decreased. These include five dimensions, such as material well-being, health and safety, education, behaviours and risk exposure, housing and environment.. Alongside these indicators this chapter will explore others, namely family’s incomes, child protection services data, health, and education rates of Southern European countries. Finally, a case study on child poverty in Portugal and on the crisis in children’s perspectives will be discussed.